Kobieta a socjalizm : marksistowska wizja miejsca kobiet w państwie, prawie i społeczeństwie - Sydor, Paweł (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Marxism is a philosophical movement that, according to its founders – Karl Marx and Friedrich Engels – was intended to discover objective historical truths. Discovery thereof begets both knowledge and a political program. Apart from the concepts of base (i.e. economic foundation) and substructure (i.e. broadly understood culture), Marxism introduces the notions of alienation and exploitation of labor – phenomena that are constantly present in societal relations in formations based on private ownership of the means of production. These phenomena are objective in nature and concern the classes who do not own the means of production; in capitalism this particularly refers to the proletariat. Only transitioning to communism – for which prior socio-economic formations within which the means of production are developed and level of productivity increased are necessary – eliminates the exploitation and alienation of labor, making humankind happy. Women in this march of history are imposed upon twice – first by economic oppression and second by cultural oppression created by the ruling class. Women of the exploited classes are workers and, simultaneously, persons responsible for raising children and caring for them. Meanwhile, women of the exploiting classes – although they do not do professional work – are also responsible for matters concerning child rearing and often stay married due to economic considerations. In compliance with Marxism, collectivizing social processes, including childcare and housework, will free women from economic and social slavery [...]
Keywords: marksizm; kobiety; komunizm; feminizm; emancypacja